Retratos transviados: uma leitura política da construção midiática de corpos dissidentes - Hampshire, Maria Paula Santiago (2023)
The aim of this master's dissertation is to present a preliminary mediatic construction of the dissident bodies that fabulate the fluidity of gender within the queer universe. To this end, it strolls through an empirical corpus composed especially of photographs, from which, these misguided bodies are constituted. As a theoretical foundation, the project presents bibliographies on photography, art and pain, bringing together readings by Ariella Azoulay and Susan Sontag; research on gender and sexuality - such as some works produced by Judith Butler - and articles and books that built the theory corpusmedia, by Helena Katz and Christine Greiner. The corpusmedia theory underpins this dissertation, since it considers the body as a process always unfinished and in constitution, where the instancies of biology and culture are blurred, without a priori models. The expected result is to collaborate with discussions that do not consider the modifications of the queer body as a fantasy or mere stereotypes, but rather as the constitution of singularities that trigger subjectivities and ways of life.